Pandhita Shamans and Preservation of Local Culture (Study of the Tengger Tribe in Wonokitri Village) - Setiaini, Riska Dwi; Ganefo, Akhmad (Laboratorium Sosiologi FISIP Universitas Jember, 2019)
This research was motivated by the formation of a conservative attitude and consistency of the Tengger Wonokitri tribe in carrying out traditional rituals and living habits according to ancestral teachings. This consistent life attitude is influenced by the existence of the dukun Pandhita who is known as the leader of traditional rituals. Moreover, Dukun Pandhita gives social control to his community. In the reality of Tengger tribe Wonokitri's life, people face the influence of modernity and tourism. Therefore, local cultural preservation efforts are essential to do. This study aims to determine and describe the role of the dukun Pandhita in social control as an effort to preserve the local culture of the Tengger tribe in Wonokitri Village. By using qualitative research methods and ethnographic approaches, researcher gain the data. The technique used to determine the informant is the snowball technique. The results showed, in the effort to preserve the local culture, Pandhita shamans planted value and preventive through traditional rituals and daily living habits. Besides, there are efforts to repress social control in the form of planting cultural values to uphold the law of Karma Pala. Keywords: Dukun Pandhita, Tengger tribe, Preservation of Local Culture. Referensi: Hidayat, K & Widjanarko, P. 2008. Reinventing Indonesia Menemukan Kembali Masa Depan Bangsa Jakarta:Mizan M.S, Basrowi. 2005. Pengantar Sosiologi. Bogor:Ghalia Indonesia Poloma, M. M. 2010. Sosiologi Kontemporer.Jakarta: Rajawali Pers. Ritzer, G. 2001. Sosiologi Ilmu Berparadigma Ganda.Jakarta: PT Rajawali Press Sutarto. Ayu. 2007. Saya Orang Tengger Saya Punya Agama. Jember. Kompyawisda Jatim. Zaitun. 2016. Sosiologi Pendidikan (Teori dan Aplikasi). Pekanbaru: Kreasi Edukasi. Profil Desa Wonokitri tahun 2018 Moeis, Syarif. (2008). Strukur Kekuasaan: Kekuasaan, Wewenang dan Kepemimpinan. Bandung. Universitas Pendidikan Indonesia. [27-07-2019]